2020
DOI: 10.3389/fped.2020.00487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nasal Continuous Positive Airway Pressure on Cerebral Hemodynamics in Preterm Infants

Abstract: Background: To evaluate the effects of pressure levels on cerebral hemodynamics in premature infants receiving nasal continuous positive airway pressure (nCPAP) during the first 3 days of life. Methods: Forty-four preterm infants treated with nCPAP were divided into two groups: very preterm infants [gestational age 1 (GA1), GA < 32 weeks, n = 24] and moderate/late preterm infants (GA2 group, GA 32-37 weeks, n = 20). During monitoring, pressure levels were set at 4→6→8→4 cmH 2 O, and cerebral hemodynamics was a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Another risk factor for development of IVH is hypocapnia. Hypocapnia in premature infants is associated with poor neurodevelopmental outcome, including periventricular leukomalacia (PVL), IVH, and cerebral palsy possibly due to cerebral vasoconstriction, decreased CBF, and decreased cerebral oxygen delivery to infants (34)(35)(36). Our study, comparable to another (37) showed significant increase in of IVH in neonates exposed to hypocapnia.…”
Section: Discussionsupporting
confidence: 63%
“…Another risk factor for development of IVH is hypocapnia. Hypocapnia in premature infants is associated with poor neurodevelopmental outcome, including periventricular leukomalacia (PVL), IVH, and cerebral palsy possibly due to cerebral vasoconstriction, decreased CBF, and decreased cerebral oxygen delivery to infants (34)(35)(36). Our study, comparable to another (37) showed significant increase in of IVH in neonates exposed to hypocapnia.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, neonatal respiratory distress syndrome, a common condition in premature babies, and its treatment through non-invasive respiratory support, may affect cerebral perfusion. A recent study on nasal continuous positive airway pressure (nCPAP), one of the most frequent ventilation methods used in NICU, analyzed the effects of high pressure on cerebral hemodynamics, stating that cerebral perfusion remains relatively stable when the pressure is set between 4 and 8 cmH 2 O ( Zhou et al, 2020 ).…”
Section: Cerebellar Neuropathologymentioning
confidence: 99%